2015
DOI: 10.1186/s12909-015-0284-7
|View full text |Cite
|
Sign up to set email alerts
|

Graduate entry and undergraduate medical students’ study approaches, stress levels and ways of coping: a five year longitudinal study

Abstract: BackgroundIncorporating graduate students into undergraduate medical degree programs is a commonly accepted practice. However, it has only recently been recognized that these two types of students cope with their studies in various ways. The aim was to compare the learning approaches, stress levels and ways of coping of undergraduate (UG) and graduate entry medical students (GEMP) throughout their medical course.MethodsFrom 2007–2011 each of the five year cohorts of undergraduate and GEMP students completed fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1
14

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 38 publications
2
24
1
14
Order By: Relevance
“…In agreement with previous studies, which have shown differences in both motivational variables and approaches to learning in GEM vs . DEM (e. g. Sandover et al) [9], this study has also demonstrated differences between both student groups in relation to preferred mode of instruction and perceived relationship between anatomy and clinical education.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…In agreement with previous studies, which have shown differences in both motivational variables and approaches to learning in GEM vs . DEM (e. g. Sandover et al) [9], this study has also demonstrated differences between both student groups in relation to preferred mode of instruction and perceived relationship between anatomy and clinical education.…”
Section: Discussionsupporting
confidence: 54%
“…Significant differences across motivational variables as well as approaches to learning have been identified between DEM and GEM students (e. g. Sandover et al.) [9]. As the nature of medical training and academic clinical training pathways continue to evolve, it is important that the learning requirements and educational preferences of graduate entrants are also evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of a textbook was clearly a concern and a source of confusion for these students. This finding is not unique; other studies conducted with beginning Medical and Oral Hygiene students have highlighted the same concern . It could be argued that understanding the difference between absorbing a single ‘truth’ from a textbook and being able to accommodate slightly different information on the same topic from a range of sources is a threshold concept.…”
Section: Resultsmentioning
confidence: 83%
“…However, if the student's coping strategies are not sufficient, adaptation to the new culture would be more difficult. [11][12][13][14][15][16][17][18] The disease-health patterns of different countries affect the content of medical education programs, their languages, and the type of communication between doctor and patient. The undergraduate medical education programs have a different character compared to other college programs in this regard.…”
Section: Introductionmentioning
confidence: 99%